Social and environmental analysis of food waste abatement via the peer-to-peer sharing economy - Tamar Makov (Nature Portfolio, 2020)
Reducing food waste is important. Here the authors investigate whether digitally enabled social networks can efficiently reduce food waste and find that in 19 months, around 91t of food waste were collected by secondary consumers and diverted from disposal.